Bromeliad-associated mosquitoes from Atlantic forest in Santa Catarina Island, southern Brazil (Diptera, Culicidae), with new records for the State of Santa Catarina - Müller,Gerson Azulim (2006)
Bromeliad-associated mosquitoes (Diptera: Culicidae) in Atlantic Forest in Florianópolis, Santa Catarina, southern Brazil, were studied, examining plants of Vriesea philippocoburgi Wawra and Aechmea lindenii (E. Morren) Baker var. lindenii at secondary Atlantic rain forest, and A. lindenii and Vriesea friburgensis Mez var. paludosa (L. B. Smith) at "restinga" per month, during 12 months. No immature forms of mosquitoes were collected from A. lindenii in the secondary forest. Collections obtained 368 immature mosquitoes, none of them from A. lindenii from rain forest. Culex (Microculex) spp. constituted 79.8% of the total, Wyeomyia (Phoniomyia) spp. 17.93%, and Anopheles (Kerteszia) cruzii (Dyar & Knab, 1908) only 1.36%. The study shows the great predominance of species of medical importance not yet proved, and the small number of immature stages of anopheline mosquitoes. The rainfall, but not the mean temperatures, significantly influenced the quantity of mosquitoes from V. philippocoburgi. Significant differences between the quantities of immature forms of all the bromeliad species were found, and the shape of the plants could be important to the abundance of mosquitoes. All six species of Cx. (Microculex) found are recorded for the first time in the State of Santa Catarina, and all six species of Wyeomyia (Phoniomyia) are recorded for the first time in bromeliads in this state.